2008
DOI: 10.1080/00365520701858470
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life is impaired in patients with peristomal bulging of a sigmoid colostomy

Abstract: QoL evaluated with a general and disease-specific instrument (SHS) was significantly impaired in patients with bulging around a sigmoidostomy. The Stoma-QoL questionnaire showed a small but statistically significant difference between patients with and those without bulging but the clinical significance is uncertain. Further studies are required to evaluate the role of some of the individual items in the Stoma-QoL questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 10 publications
3
83
0
4
Order By: Relevance
“…Unfortunately, patients who are symptomatic from a PSH often suffer from poor quality of life [39,44]. In one study evaluating the effects of peristomal bulging and subsequent quality of life, patients reported significant impairment in quality of life regarding symptom load, worry, and general sense of well-being.…”
Section: Quality Of Life and Financial Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, patients who are symptomatic from a PSH often suffer from poor quality of life [39,44]. In one study evaluating the effects of peristomal bulging and subsequent quality of life, patients reported significant impairment in quality of life regarding symptom load, worry, and general sense of well-being.…”
Section: Quality Of Life and Financial Impactmentioning
confidence: 99%
“…Pain and discomfort is generally caused by stretching of the abdominal wall and adjacent skin. Difficulty with maintaining a seal between the ostomy appliance and the stoma is secondary to periodic peristomal bulging [39]. As a result, leakage around the stoma appliance may be frequent, resulting in significant peristomal dermatitis and difficulty concealing the ostomy under clothing.…”
Section: Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Kald et al (2008) found body image to be of great concern for PSH patients as the bulge, particularly with difficulties in staying away from home overnight and anxieties about the proximity of the toilet. Expert opinion suggests nurses play a pivotal role in alleviating these concerns by finding a suitable stoma appliance, teaching and supporting ostomists to enable them to live with a PSH by discussing the options and help available (Black, 2009).…”
Section: Physical Costmentioning
confidence: 99%
“…We know that the definition used in our trial has clinical relevance and may reflect the reality faced by patients and stoma therapists [4]. We chose this definition as we also regarded it to be simple and reproducible.…”
mentioning
confidence: 99%